Troesmis város törvénye a Kr. u. 2. század végéről = The municipal charter of Troesmis from the end of the 2nd century AD - Illés Imre Áron (Belvedere Meridionale, 2019)
The fragments of the lex municipalis Troesmensium – two almost intact bronze tablets – were found by illegal treasure-hunters in 2002 and were reclaimed by the Romanian state in 2015. The complete text with introduction, commentaries and German translation was published in 2016. This small contribution contains the Hungarian translation of the text with introduction, short commentaries and some suggestions for the better understanding of the charter.